Synthesis, structure, physical properties, and displacement current measurement of an n-type organic semiconductor: 2:3,5:6-Bis(1,1-dicyanoethylene-2,2-dithiolate)-quinone - Xiao, Jinchong (2013)
An n-type organic semiconductor 2:3,5:6-bis(1,1-dicyanoethylene-2,2-dithiolate)-quinone (BDQ) has been successfully synthesised and characterised. The single crystal structure of BDQ, determined by single-crystal X-ray crystallography, indicated that BDQ is a planar molecule with strong face-to-face π-π stacking (3.40 Å) and S···S interactions (3.66 Å) between neighbouring molecules, which might be in favour of the effective charge transport. The UV-vis spectrum shows that BDQ has shoulder absorption up to 550 nm (2.25 eV). The electrochemical property displays that the HOMO-LUMO gap of BDQ obtained from the half-wave redox potential is 1.92 eV. The displacement current measurement of BDQ-based devices is demonstrated and discussed.